Social integration among multi-ethnic students at selected Malaysian universities in Peninsular Malaysia: a survey of campus social climate - Ramlee Mustapha,; Norzaini Azman,; Faridah Karim,; Abdul Razak Ahmad,; Maimun Aqsha Lubis, (Penerbit Universiti Kebangsaan Malaysia, 2009)
Institutions of higher education are expected to be beacons for harmony, bridging racial differences and promoting an atmosphere of reason, inquiry and collegiality. Institutions of higher education are in a unique position to address the teaching and learning of diversity by creating an environment that will allow positive interaction among students from different ethnicities and backgrounds. Thus, the purpose of this article is to report the results of an empirical study on campus social climate as perceived by Þrst- and Þnal-year undergraduates. The Campus Social Environment Survey is employed to gauge various aspects of cross-racial interaction among undergraduates in both private and public institutions of higher learning. The initial analysis focuses on descriptive data on four main constructs of racial integration ― accommodation, acculturation, assimilation and amalgamation. Implications and recommendations for teaching and learning as well as for future research are presented and discussed